2003
DOI: 10.1037/0096-1523.29.5.1036
|View full text |Cite
|
Sign up to set email alerts
|

Absence of perceptual processing during reconfiguration of task set.

Abstract: The authors manipulated stimulus contrast and response-stimulus interval in the alternating runs paradigm to investigate whether early processing could be carried out during a task switch. Subjects alternated between judging the magnitude and the parity of a digit. The results suggested that early processing was not carried out during the task switch (Experiment 1), even in the absence of potentially confounding auditory or visual warning signals (Experiment 2). This processing was, however, carried out in par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
115
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(133 citation statements)
references
References 47 publications
15
115
3
Order By: Relevance
“…On the other hand, the impact of changes in stimulus contrast on RT are predicted to decrease at short inter-stimulus-intervals (Van Selst et al 1999;Oram et al 2002;Oriet & Jolicoeur 2003). The mean reaction times in the experimental study ( Figure 6) were in agreement with the predicted pattern of results.…”
supporting
confidence: 81%
“…On the other hand, the impact of changes in stimulus contrast on RT are predicted to decrease at short inter-stimulus-intervals (Van Selst et al 1999;Oram et al 2002;Oriet & Jolicoeur 2003). The mean reaction times in the experimental study ( Figure 6) were in agreement with the predicted pattern of results.…”
supporting
confidence: 81%
“…Interestingly, the underadditivity of the interaction disappears when stimulus degradation is used in a task-switching paradigm. Oriet and Jolicoeur (2003), using an alternating runs paradigm in which participants judged digits for parity and magnitude as in our experiments, observed that the effect of stimulus degradation did not differ as a function of whether participants switched or repeated tasks. From the additive effects of task switching and degradation, the authors concluded that task switching may impose a hard bottleneck even for early stimulus processing.…”
Section: Discussionmentioning
confidence: 99%
“…Now, it is important to note that in our continuous span procedure, participants must not only switch back and forth between parity and magnitude judgments but also from maintenance activities to digit processing at stimulus onset. What is demonstrated by Oriet and Jolicoeur (2003) is that early processing of digits waits until task set reconfiguration or whatever operation responsible for the task switch cost is completed. Thus, it can be assumed that stimulus degradation within our paradigm induced a prolonged occupation of attention that resulted in the predicted impairment of maintenance and recall.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, experimental paradigms measured switching at the judgment level (as in the vast majority of task-switch studies; e.g., Altmann, 2004;Arrington & Logan, 2004;Dreisbach, Haider, & Kluwe, 2002;M. Hübner, Kluwe, Luna-Rodriguez, & Peters, 2004;Koch, 2001;Lien, Schweickert, & Proctor, 2003;Logan & Bundesen, 2003;Logan, Schneider, & Bundesen, 2007;Mayr & Kliegl, 2000;Meiran, 1996;Nieuwenhuis & Monsell, 2002;Oriet & Jolcoeur, 2003;Rogers & Monsell, 1995;Schneider & Logan, 2006;Waszak, Hommel, & Allport, 2003), at the stimulus dimension level (e.g., R. Hübner et al, 2001;Mayr & Keele, 2000), at the level of the responses (in terms of response sets; e.g., Philipp & Koch, 2005), and at the level of (pure) stimulus-response mappings (e.g., Rushworth et al, 2002Rushworth et al, , 2005Shaffer, 1965).…”
Section: Types Of Tasks and A First Modelmentioning
confidence: 99%